(untitled) (CIPEEX, 2025)
The adoption of outdated practices, poor management, and lack of knowledge are factors that prevent many family members and acquaintances who are cattle ranchers from achieving efficiency in the management of beef cattle farming. Ease, organization, and productivity are essential for success in managing the property, especially in controlling livestock and finances. However, the insistence on traditional methods, such as using paper and pen, becomes the biggest obstacle, causing stress and losses instead of performance. To solve these problems, technology emerges as a solution. AgroGestão software, currently in its initial phase, aims to bring simplicity and agility to agricultural activities, allowing for control, planning, and efficiency in tasks related to the management of the property, livestock, and finances. Furthermore, a feature designed for AgroGestão is a space to store contacts of professionals, workers, and suppliers needed for services such as caretakers, veterinarians, as well as for the purchase of products and equipment for the land and livestock. Still in its design and improvement phase, AgroGestão’s main goal is to support the performance of cattle ranchers, also facilitating the hiring of labor and the acquisition of essential inputs for animal welfare and soil fertility. To develop these features, it was necessary to analyze data from family members, known cattle ranchers, and other professionals in the sector, as well as conduct research on the challenges faced in beef cattle farming. Based on the information gathered, AgroGestão, in its enhancement and early development phase, aims to solve common problems, allowing cattle ranchers to input data, manageexpenses, monitor herds, plan purchases and sales, conduct financial analyses, and access relevant information about agribusiness. This helps to prevent losses and reduce stress in property management. Moreover, the software makes it easier to hire professionals and purchase equipment, benefiting both the cattle ranchers and others involved in the sector. Therefore, AgroGestão, still under development, has the ultimate goal of optimizing beef cattle management, preventing losses, and promoting more efficient performance, enabling cattle ranchers to achieve their goals and dreams.